2019
DOI: 10.21791/ijems.2019.1.46.
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fluxes on the Melt Quality of AlSi7MgCu Alloy

Abstract: The presence of inclusions such as oxides, carbides or refractory particles can be harmful to the mechanical and surface characteristics of castings. Inclusion-rich metals result in lower fluidity and feeding capability during casting. Nowadays, solid fluxes are widely used in foundries in order to reduce the inclusion content of aluminium melts. In this study, the effect of four different fluxes on the melt quality was studied. First, the inclusion content of the flux-treated melt, and then the properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
(8 reference statements)
1
6
0
Order By: Relevance
“…From the results of this work, it can be concluded that the refining efficiency of different fluxes is highly dependent on their chemical composition, melting temperature, and wettability with aluminum oxide, which agrees with the conclusions of Gyarmati et al [ 15 ]. The ten fluxes in this work all have significantly lower melting temperatures than the refining temperature, which is a prerequisite to enable the fluxes to have a refining effect in the melt.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…From the results of this work, it can be concluded that the refining efficiency of different fluxes is highly dependent on their chemical composition, melting temperature, and wettability with aluminum oxide, which agrees with the conclusions of Gyarmati et al [ 15 ]. The ten fluxes in this work all have significantly lower melting temperatures than the refining temperature, which is a prerequisite to enable the fluxes to have a refining effect in the melt.…”
Section: Resultssupporting
confidence: 91%
“…An OCA25–HTV 1800 was used for the high-temperature contact angle test. According to Gyarmati [ 15 ], Li [ 18 ], Chen [ 27 ], Wan [ 28 ], and Fu et al [ 9 ], the most common oxide inclusions within the aluminum melt are aluminum oxide. Because the aluminum oxide inclusions within the aluminum melt show an amorphous state, taking the form of strings and films, it is hard to study the contact angle between the fluxes and the actual aluminum oxide.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where K is the K-mold value (dimensionless number), n is the number of examined fracture surfaces, and S is the total number of inclusions found in n pieces [35,36]. The surface of the found inclusions was investigated with a Zeiss EVO MA 10 scanning electron microscope (SEM) equipped with an energy-dispersive X-ray spectroscopy (EDS) system.…”
Section: Melt Quality Assessmentmentioning
confidence: 99%
“…The mechanism is the improvement of fluidity due to the heat released by exothermic reactions [21]. Moreover, when added with fluorides, the heat released facilitates the chemical reactions between fluorides and inclusions [34]. Examples of oxidizing agents include nitrates such as KNO 3 and NaNO 3 , carbonates such as CaCO 3 and K 2 CO 3 and sulfates such as K 2 SO 4 and Na 2 SO 4 [24].…”
Section: Oxidizing Agentsmentioning
confidence: 99%